Review of Flood Hazards Studies in Nepal - Shrestha, Buddhi Raj; Rai, Raj Kumar; Marasini, Saroj (The Geographic Base, 2020)
Flood, a common water-induced disaster of monsoon season, is a recurring phenomenon in Nepal. It causes many deaths and injuries besides severe impacts on the vital infrastructures of the nation. This paper reviews the published national and international journal articles related to flood hazard mapping in Nepal. Desinventar database from 1971-2016 shows that Bagmati province and province 2 are more affected than other provinces in Nepal. Here we review the previous studies on flood disasters at the regional and national levels. The results show that most of the papers are based on a steady flow model for inundation mapping and more focuses on hazard analysis rather than vulnerability and risk assessment.